Pengembangan E-LKPD Berbasis PjBL-STEM Pada Pokok Bahasan Asam Basa - Purnamasari, Ni Nyoman Dayuni; Anwar, Yunita Arian Sani; Junaidi, Eka (FKIP University of Mataram, 2025)
This study aims to develop an e-LKPD based on Project-Based Learning (PBL) integrated with the STEM (Science, Technology, Engineering, and Mathematics) approach for acid-base materials, and to determine the level of validity and practicality. This study uses an R&D development method (Research and Development) 4D model (Define, Design, Develop, and Disseminate). The characteristics of the e-LKPD developed are aimed at catering to students' learning interests, with four key features: contextual, simple projects, gamification, and audio-visual elements. The subjects of the study consisted of 32 students of class XI Phase F at SMAN 6 Mataram. Validity analysis was conducted using the Aiken index (V), which yielded a value of 0.92, indicating that the e-LKPD developed was classified as highly valid. The level of practicality was measured through teacher and student responses of e-LKPD, with a percentage result of 92.95%, which was in the very practical category. Thus, the results of this study indicate that the e-LKPD PjBL-STEM developed has met the criteria of high validity and practicality, making it suitable for use in schools to learn about acid-base materials.